Synthesis of monomers of γ-polyamide nucleic acids mimics - A. V. Dezhenkov; M. A. Lyanov; D. I. Prokhorov; N. E. Lysenko; O. V. Esipova; Yu. G. Kirillova (Тонкие химические технологии, 2011)
Universal efficient preparative approach for obtaining of γ-substitued polyamide DNA-mimics on the base of L-alanine and L-glycine derivates was presented. As result of research cytosine and adenine-containing final monomers were synthesised. It was found that both allyl and methyl C-terminal protecting group can be used in the synthesis as example of cytosine-containing derivates.